Evaluasi Kuat Tumpu Alat Sambung Baut pada Papan WPC dari Limbah Sengon dan Plastik HDPE - Arnandha, Yudhi; Satyarno, Iman; Awaludin, Ali; Fardhani, Arfiati (MEDIA KOMUNIKASI TEKNIK SIPIL, 2016)
Wood Plastic Composite (WPC) is wood based material that been produce by mixing sawdust as main composition and plastic polymer as bonding agent. Nowadays, WPC board already been produced in Indonesia using Sengon sawdust and recycle HDPE plastic. Sengon sawdust was used as WPC since its availability from plywood production waste, moreover HDPE plastic considered had higher strength and more rigid than PET plastic. WPC occasionally being used as non structural material, moreover from previous study about mechanical properties of WPC, it was found that WPC Sengon has high shear strength around 25 – 30 MPa. These lead that WPC Sengon had a potential used as shear wall sheathing, thus additional research need to be conducted in order to study the type of bolt and diameter of the bolt can be used for these shear wall. This study aimed to investigate the dowel bearing of bolt using full hole method based on ASTM D5764 with type and bolt diameter as specimen variation. Two types of bolt were used in this study; stainless bolt and standard bolt with diameter each of 6 mm, 8 mm, 10 mm and 12 mm. According to ANOVA, there was insignificant result between stainless bolt and standard one, but there was significant result based on diameter of the bolt. Hereafter, it can be recommended the used of 10 mm diameter of bolt for structural purpose with dowel bearing strength around 67 – 70 MPa.